Representation of Social Issues in Indian Graphic Novels - Singh, Punyaprada; George, Mercy (Bodhi: An Interdisciplinary Journal, 2024)
The study intends to uncover the significant commentary these works offer on current themes like gender dynamics, caste discrimination, governmental corruption, religious tensions, and the challenges of modernity, by analyzing a varied spectrum of graphic novels coming out of the subcontinent. We shed light on how these graphic novels not only represent the socio-political environment of India but also question and modify narratives by combining qualitative content analysis and in-depth case studies. Our research highlights the importance of graphic novels as effective social critique mediums in India, echoing wider global trends where visual storytelling goes beyond just amusement to provide insightful social commentary